Cross-Sectoral Governance in Combating Online Gambling: A Stakeholder Theory Perspective - Adillah , Muhammad Arief; Tando, Cahyoko Edi (Moestopo International Review on Social, Humanities, and Sciences, 2026)
Gambling has become a classic problem in Indonesia, from the early history of independence to the present day. If there is neglect in this condition, it is certain that there will be a negative impact on the general public. This study will use a qualitative method using informants from the perspective of immigration officers. Data collection was carried out using interview methods and documentation in the form of relevant scientific articles. The theory used is the stakeholder theory. The results of the study indicate that cross-sectoral partnerships need to be attempted that must involve Immigration, then there needs to be an evaluation of the online gambling eradication task force policy currently being implemented by the Ministry of Communication and Information, on the other hand there must be involvement of the community and community leaders that need to be considered and interpersonal communication within the family must be prioritized. The limitation of this study is to review the effectiveness of formal legal rules and policies regarding the eradication of online gambling, so that future research can answer the limitations of this study.